Creation and maintenance of variation in allorecognition loci - Nydam, Marie L.; De Tomaso, Tony (Frontiers in Immunology, 2011)
Allorecognition is the ability of an organism to differentiate self or close relatives from unrelated individuals. Effective allorecognition systems are critical to the survival of organisms; they prevent inbreeding, protect against pathogens, and facilitate fusions between close relatives. Where the loci governing allorecognition outcomes have been identified, the corresponding proteins often exhibit exceptional polymorphism. Two important questions about this polymorphism remain unresolved: how is it created, and how is it maintained. Studies on the evolution of polymorphism in allorecognition loci have traditionally been restricted to the Major Histocompatibility Complex (MHC). But because the genetic bases of several allorecognition systems have now been identified, including alr2 in Hydractinia, FuHC in Botryllus, the het (vic) loci in fungi, lagB1 and lagC1 in Dictyostelium, and self-incompatibility (SI) loci in several plant families, we are now poised to achieve a clearer understanding of how these loci evolve. In this review, we summarize what is currently know about the evolution of allorecognition loci, highlight open questions, and suggest future directions.